When good deals need help getting done: Articulating side payment strategies. Issue 6 (December 2021) - Fox, Brian C.; Grove, Sergio; Souder, David
Abstract: Value creation often requires coordinated action by multiple firms. Existing research on value-based strategy emphasizes situations where both parties reasonably anticipate sharing the gains to cooperation and develop arms-length contracts through bargaining. Less existing research on value-based strategy addresses situations where value-creating market transactions fail to occur because one party expects to be worse off from coordinated action, precluding their participation. Although vertical integration or informal contracts potentially overcome this reticence, these solutions are not always feasible or incur costs of their own. We model how firms may be able to strike a stable deal and create value by employing a side payment strategy. This technique mitigates transactional frictions by playing a biform game with a cooperative first stage, which modifies the payoffs in a non-cooperative second stage so that coordinated action becomes feasible in a stable agreement. We also extend the basic analysis to consider variations in contract enforceability, reneging, and presence of multiple counterparties.